2022
DOI: 10.1016/j.jbc.2022.101650
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of Linum usitatissimum hydroxynitrile lyase: A new cyanohydrin decomposition mechanism involving a cyano-zinc complex

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 87 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…Many HNLs possess diverse primary structures due to the scarcity of homologies among their amino acid sequences, based on which HNLs are classified into seven superfamilies, including α/β-hydrolases fold (AtHNL, BmHNL, HbHNL, MeHNL, and SbHNL), Bet v1 like fold (DtHNL), cupin (AcHNL, BpHNL, GtHNL, and PsmHNL), dimeric α+β barrel (PeHNL), FAD-binding oxidoreductase (EjHNL, PaHNL, PmHNL, and PsHNL), lipocalin-like fold (ChuaHNL and PlamHNL), and Zn 2+ -containing alcohol dehydrogenase (LuHNL). 116,117…”
Section: Nitrile Biosynthesis In Plantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many HNLs possess diverse primary structures due to the scarcity of homologies among their amino acid sequences, based on which HNLs are classified into seven superfamilies, including α/β-hydrolases fold (AtHNL, BmHNL, HbHNL, MeHNL, and SbHNL), Bet v1 like fold (DtHNL), cupin (AcHNL, BpHNL, GtHNL, and PsmHNL), dimeric α+β barrel (PeHNL), FAD-binding oxidoreductase (EjHNL, PaHNL, PmHNL, and PsHNL), lipocalin-like fold (ChuaHNL and PlamHNL), and Zn 2+ -containing alcohol dehydrogenase (LuHNL). 116,117…”
Section: Nitrile Biosynthesis In Plantsmentioning
confidence: 99%
“…Many HNLs possess diverse primary structures due to the scarcity of homologies among their amino acid sequences, based on which HNLs are classied into seven superfamilies, including a/b-hydrolases fold (AtHNL, BmHNL, HbHNL, MeHNL, and SbHNL), Bet v1 like fold (DtHNL), cupin (AcHNL, BpHNL, GtHNL, and PsmHNL), dimeric a+b barrel (PeHNL), FAD-binding oxidoreductase (EjHNL, PaHNL, PmHNL, and PsHNL), lipocalin-like fold (ChuaHNL and PlamHNL), and Zn 2+ -containing alcohol dehydrogenase (LuHNL). 116,117 Cyanohydrins serve as the fundamental units for numerous reactions and also form the basis for various compounds utilized as pharmaceuticals, agrochemicals, and ne chemicals. As an efficient, environmentally friendly, and highly stereoselective biocatalyst, HNLs have received much attention for a long time.…”
Section: Hydroxynitrile Lyasementioning
confidence: 99%
“…Asano and coworkers have illustrated the catalytic mechanism of a Zn 2 + -dependent alcohol dehydrogenase superfamily HNL, Linum usitatissimum (LuHNL) by crystallizing it in its ligand-free form and in complex with acetone cyanohydrin and (R)-2-butanone cyanohydrin. [46] SDM of the catalytic residues were done and the mutational studies revealed a novel reaction mechanism for cyanohydrin decomposition involving the cyano-zinc complex and hydrogen-bonded interaction of the hydroxyl group of cyanohydrin with Glu323/Thr65 and H 2 O/ Lys162 of LuHNL. Understanding the catalytic mechanism is key to protein engineering based enzyme design for biocatalytic applications.…”
Section: Protein Engineering Of Hnls For Stereoselective Cà C Bond Fo...mentioning
confidence: 99%
“…and enantiselectivity in synthesis of nine (R)cyanohydrins [42] ChuaHNL-PpPDI SDM N99Q, N109Q, N123Q, N99Q-N109Q, N99Q-N123Q and N109Q-N123Q N123Q low protein production revealed that sugar chains are essential for the high-level production in His-ChuaHNL higher specific activity towards three of the eight aromatic aldehydes in their chiral cyanohydrin synthesis [43] ChuaHNL SDM R38A, Y40F, D56E, Y103F and K117R lost or decreased activity in cyanogenesis and cleavage of (R)-MN [44] PlamHNL SDM PlamHNL-N85Y higher enantioselectivity and conv. in (R)-2-Cl-MN synthesis [45] LuHNL SDM SDM of the catalytic residues elucidated a novel reaction mechanism for cyanohydrin decomposition involving the cyano-zinc complex and hydrogen-bonded interaction of the hydroxyl group of cyanohydrin with Glu323/Thr65 and H 2 O/Lys162 of LuHNL [46] GtHNL SDM (based on results of epPCR and SSM)…”
Section: Enantioselective Cleavagementioning
confidence: 99%
“…We recently reported the X‐ray structures of new HNLs from the millipedes C. hualienensis [2c] and Parafontaria laminata [2d] belong to the lipocalin‐like fold. The HNLs identified to date can be classified into seven superfamilies [3a] that include lipocalin, glucose–methanol–choline (GMC) oxidoreductase, [3b] α/β‐hydrolases, [3c,d] cupin, [3e] Bet v1, [3f] dimeric α+β barrel folds, [3g] and Zn 2+ ‐dependent alcohol dehydrogenase [3]…”
Section: Introductionmentioning
confidence: 99%